2001
DOI: 10.1093/her/16.6.735
|View full text |Cite
|
Sign up to set email alerts
|

Can health professionals learn qualitative evaluation methods on the World Wide Web? A case example

Abstract: The Enhancing Data Utilization Skills through Information Technology (EDUSIT) project trained Maternal and Child Health professionals to collect, analyze and interpret data via a year-long web-based course. The overall goal of the project was to strengthen the technology and analytic skills of the public health workforce. This article describes and analyzes a web-based module for training public health professionals to use qualitative research and evaluation methods that was one of six offered within the EDUSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 18 publications
0
16
0
6
Order By: Relevance
“…We identified public health training programs delivered in over 11 countries: Australia, 10,16,17 Bolivia, 18 Brazil, 19 Canada, [20][21][22] Greece, 23 the Islamic Republic of Iran, 24 Mexico, 25 Rwanda, 26,27 Uganda, 28 the United Kingdom 29 and the United States of America (USA). [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] One program offered trainings in over 77 countries, 46 and another trained participants in Austria, Lithuania and the Netherlands. 9 Within the past 7 years, 19 of these articles were published.…”
Section: Public Health Training Program Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified public health training programs delivered in over 11 countries: Australia, 10,16,17 Bolivia, 18 Brazil, 19 Canada, [20][21][22] Greece, 23 the Islamic Republic of Iran, 24 Mexico, 25 Rwanda, 26,27 Uganda, 28 the United Kingdom 29 and the United States of America (USA). [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] One program offered trainings in over 77 countries, 46 and another trained participants in Austria, Lithuania and the Netherlands. 9 Within the past 7 years, 19 of these articles were published.…”
Section: Public Health Training Program Characteristicsmentioning
confidence: 99%
“…The objectives of and the methods used to gather evaluations varied across studies. Approaches to evaluation included surveys; 26,27,38,42,43 pre/post questionnaires; 30,31,33,41 participant completion statistics; 19 interviews; 28,45 and mixed methods (a combination of either focus groups or interviews and surveys or questionnaires with participants). 9,10,[16][17][18][20][21][22][23][24][25]29,32,[34][35][36]39,40,44 Evaluations after participation captured participants' demographic information, subject knowledge before and after training, satisfaction with and post-training use of their newly gained knowledge.…”
Section: Evaluation Of Trainingsmentioning
confidence: 99%
“…[5][6][7] In North Carolina, 40% of the state's population is considered rural as classified by the U.S. Census 2000. 8 The NCCPHP assessment showed that most North Carolina public health nurses had Internet access at home (79%) or at work (89%), making a computer-based course both practical and feasible.…”
Section: Synopsismentioning
confidence: 99%
“…No differences were found in course grades; however, online students reported that they paced themselves differently (more slowly) and that this often resulted in "rushed assignment." Steckler et al 63 During the pelvic examination, if the student cannot feel the size, shape, or position of the first trimester and/or non-pregnant uterus, the preceptor can assist the student by placing a hand on the patient's abdomen over the uterus and applying firm but gentle pressure. The student is then instructed to place the two vaginal fingers in the lateral fornices to palpate for uterine size.…”
Section: Mid-term and Final Gradesmentioning
confidence: 99%